Dynamic mechanisms of strengthening and softening of coherent twin boundary via dislocation pile-up and cross-slip. Issue 8 (3rd August 2022) - Li, Zhipeng; Zhang, Jianfei; Zhai, Yadi; Zhang, Jiabao; Wang, Xiaodong; Zhang, Ze; Mao, Shengcheng; Han, Xiaodong
Abstract : Although cross-slip strongly affects the deformation of polycrystalline materials, the phenomenon is rarely studied in twinned face centered cubic (FCC) metals. Here we performed in-situ TEM nanoindentation on a twinned nickel bi-crystal. Multiple pile-ups were generated, with the first dislocations pinned at a coherent twin boundary (CTB) and multiple following dislocations cross-slipping within the matrix. Stress calculation revealed that the cross-slip events are made possible by the CTB, the first dislocations, and the favorable shear stress created jointly by external stress and dislocation interaction. These cross-slip events reduce tip stress and soften the material until inter-grain plasticity is eventually activated. IMPACT STATEMENT In-situ TEM nanoindentation reveals the characteristics of dislocation pinning, pile-ups and cross-slip along the twinning boundary in a twinned FCC metal for the first time. GRAPHICAL ABSTRACT: UF0001